Educational mission of judo - Kalina, R. M.; Jagie, W.; Kruszewski, A. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
The purpose of the work was to study and analyse the judo training programs used at different educational institutions to evaluate the impact of judo on human (athlete`s) mind.